The Encouragement and education to establish a halal-based business for indonesian migrant workers in Penang, Malaysia - Sunarti Sunarti; Nurkhasanah Nurkhasanah; Warsi Warsi; Intan Daud; Siti Hajar Salamah (Community Empowerment, 2024)
Returning workers often face challenges in identifying suitable employment upon their return to Indonesia. The objective of this initiative is to enhance the entrepreneurial skills of migrant workers in the special branch of Penang, Malaysia. Motivating them to establish businesses based on halal products is a crucial aspect of this effort, providing valuable insights and provisions for their reintegration into Indonesia. The training focuses on soybean juice production using locally sourced soybeans. Pre and post-tests were conducted before and after the activity to assess the workers' knowledge levels regarding halal product-based entrepreneurship. The pre-test results yielded a mean score of 57.26 ± 20.59 SD, while the post-test showed improvement with a mean score of 76.5 ± 8.5 SD. The results indicate a significant increase in knowledge following the training. Notably, two female workers successfully applied the soybean juice-making skills acquired during the training. In conclusion, providing motivation and training for halal product-based entrepreneurship to migrant workers is effective in enhancing their knowledge and practical skills in this field.